Testing the epidemic change in nearly nonstationary autoregressive processes - Markevičiūtė, Jurgita; Račkauskas, Alfredas; Suquet, Charles (Nonlinear Analysis: Modelling and Control, 2014)
Some tests for an epidemic type change in a first order nearly nonstationary autoregressive process are investigated. Limit distributions of the tests are found under no change. Consistencyis examined under short epidemics in the mean of innovations.
Keywords: autoregressive process; epidemic change; uniform increments statistics; test power analysis